Hypofractionated versus conventionally fractionated radiotherapy for patients with localised prostate cancer (HYPRO): final efficacy results from a randomised, multicentre, open-label, phase 3 trial. Issue 8 (August 2016) - Incrocci, Luca; Wortel, Ruud C; Alemayehu, Wendimagegn Ghidey; Aluwini, Shafak; Schimmel, Erik; Krol, Stijn; van der Toorn, Peter-Paul; Jager, Hanja de; Heemsbergen, Wilma; Heijmen, Ben; Pos, Floris
Summary: Background: Studies have reported a low α/β ratio for prostate cancer, suggesting that hypofractionation could enhance the biological tumour dose without increasing genitourinary and gastrointestinal toxicity. In the multicentre phase 3, HYpofractionated irradiation for PROstate cancer (HYPRO) trial, hypofractionated radiotherapy was compared with conventionally fractionated radiotherapy for treatment of prostate cancer. We have previously reported acute and late incidence of genitourinary and gastrointestinal toxicity; here we report protocol-defined 5-year relapse-free survival outcomes. Methods: We did an open-label, randomised, phase 3 trial at seven Dutch radiotherapy centres. We enrolled patients with intermediate-risk to high-risk T1b–T4NX–N0MX–M0 localised prostate cancer, a prostate-specific antigen concentration of 60 μg/L or less, and a WHO performance status of 0–2. We used a web-based application to randomly assign (1:1) patients to either hypofractionated radiotherapy of 64·6 Gy (19 fractions of 3·4 Gy, three fractions per week) or conventionally fractionated radiotherapy of 78·0 Gy (39 fractions of 2·0 Gy, five fractions per week). Based on an estimated α/β ratio for prostate cancer of 1·5 Gy, the equivalent total dose in fractions of 2·0 Gy was 90·4 Gy for hypofractionation compared with 78·0 Gy for conventional fractionation. The primary endpoint was relapse-free survival. All analyses were done on an intention-to-treat basis in all eligible patients. The HYPRO trial completed recruitment in 2010 and follow-up is ongoing. This trial is registered with ISRCTN, number ISRCTN85138529. Findings: Between March 19, 2007, and Dec 3, 2010, 820 patients were enrolled, of whom 804 were eligible and assessable for intention-to-treat analyses. Of these, 407 were assigned hypofractionated radiotherapy and 397 were allocated conventionally fractionated radiotherapy. 537 (67%) of 804 patients received concomitant androgen deprivation therapy for a median duration of 32 months (IQR 10–44). Median follow-up was 60 months (IQR 51–69). Treatment failure was reported in 169 (21%) of 804 patients, 80 (20%) in the hypofractionation group and 89 (22%) in the conventional fractionation group. 5-year relapse-free survival was 80·5% (95% CI 75·7–84·4) for patients assigned hypofractionation and 77·1% (71·9–81·5) for those allocated conventional fractionation (adjusted hazard radio 0·86, 95% CI 0·63–1·16; log-rank p=0·36). There were no treatment-related deaths. Interpretation: Hypofractionated radiotherapy was not superior to conventional radiotherapy with respect to 5-year relapse-free survival. Our hypofractionated radiotherapy regimen cannot be regarded as the new standard of care for patients with intermediate-risk or high-risk prostate cancer. Funding: Dutch Cancer Society.